Anemia in Pregnancy and Risk of Blood Transfusion [11C]. (May 2018) - Scholz, Rob; Young, Danielle; Scavone, Barbara; Hofer, Jennifer; Siddiqui, Maryam
Abstract : INTRODUCTION: A third of women have antepartum anemia, potentially leading to maternal and neonatal morbidity and mortality. Allogenic blood transfusion is often an appropriate treatment. Available evidence suggests antepartum correction may decrease postpartum transfusion volumes. This retrospective cohort study investigated the relationship between anemia at mid-trimester (24-28 weeks or third trimester) and estimated blood loss (EBL) and transfusion at delivery. METHODS: All deliveries between January 2014 and March 2015 at our institution were eligible for inclusion. Exclusion criteria included delivery <24 weeks gestational age and unknown mid-trimester hemoglobin. Anemia was defined as hemoglobin RESULTS: 1071 patients were included. 473 (44.16%) were anemic at mid-trimester and 36 (3.36%) required postpartum transfusion. Of patients non-anemic at mid-trimester, 7% were anemic at delivery compared to 57% of those who were anemic at mid-trimester (p<0.001). Five (0.84%) non-anemic patients required transfusion compared to 31 (6.55%) anemic patients (p=<0.001). Of transfused patients, EBL was higher in non-anemic compared to anemic patients (mean EBL 2520.00+/-962.81ml vs. 1601.45+/-1464.38ml, p=0.04). Mean transfusion volume did not differ (not anemic 3.60+/-1.67 vs. anemic 2.67+/-2.44, p=0.011). CONCLUSION: Patients with anemia at mid-trimester were significantly more likely to be anemic at delivery. These patients had higher rates of postpartum blood transfusion despite lower EBL than non-anemic patients. The trend toward lower transfusion volume for anemic patients suggests that these may be preventable. Treatment of anemia at mid-trimester is essential.